Acute effects of restraint, shock and training in the elevated T-Maze on noradrenaline and serotonin systems of the prefrontal cortex (2014)
The prefrontal cortex (PFC) participates in cognitive functions and stress regulation. Noradrenaline (NA) and serotonin (5-HT) levels in some regions of the central nervous system are modified by acute stress. The effects depend on the type of stressor and the time elapsed between the presence of the stressor and the assessment. The aims of the present study were to assess the acute effect of different stressors on NA and 5-HT activities in the PFC and its relation with corticosterone levels. Independent groups of male Wistar rats (250-280 g) were submitted to restraint, footshock or training in the elevated T-maze (ETMT). The animals were sacrificed immediately (T0) or one hour (T1) after stress exposure. An untreated group sacrificed concurrently with treated animals was included as control. Samples of the PFC were dissected and the concentration of NA, 5-HT and their metabolites were measured by HPLC. Corticosterone levels were measured in serum. None of the treatments modified NA levels in the PFC. Animals exposed to footshock or ETMT showed significantly higher concentrations of 5-HT at T0. Restraint and footshock treatments were associated with higher corticosterone levels at T0 and T1 after the respective treatment. Taken together the results show that in the PFC, the noradrenergic and serotonergic systems, and the corticosterone levels respond in different ways to different stressors.